Hodnocení klinické ucinnosti a toxicity rezimu FND (fludarabin, mitoxantron, dexamethason) u pacientů s folikulárním lymfomem - Oborilová, A; Mayer, J; Korístek, Z; Hofmanová, Z; Vásová, I; Navrátil, M; Vinklárková, J; Muzikárová, M; Klabusay, M; Matuska, M (Casopis lekaru ceskych, 2004)
BACKGROUND: One of the perspective therapeutic possibilities in follicular lymphomas (FL) is the fludarabine-based regimen FND (fludarabine, mitoxantron, dexamethason). However serious signs of myelotoxicity and significant immunosuppression with appearance of the opportunistic infections were described after the fludarabine treatment. METHODS AND RESULTS: Follicular lymphoma patients with advanced disease grade I-II were treated with FND (6-8 cycles). The immunotoxicity was evaluated by measuring of immunoglobuline levels (IgA, IgG, IgM) and that of lymphocytes subpopulations (CD3+, CD4+, CD8+, CD20+, CD56+) in peripheral blood. The myelotoxicity was evaluated by cultures of progenitor cells (CFC and LTC-IC). Totally 34 patients (median age 55.5 years) were evaluated, the overall response was 72% (CR 61%, PR 11%, progression 28%). 73% patients of 11 after 6-8 FND show persisting CR (27% relapsed) with median follow-up about 15 months. The dominating toxicity was myelotoxicity. The leucopenia grade III-IV occurred in about 30% cycles. Because of toxicity it was necessary to reduce doses of FND in 10% cycles and this treatment had to be finished ahead of schedule in 29% patients. The significant immunotoxicity was found only in the decrease of whole lymphocyte population (p < 0.05) and of IgG level (p < 0.05). The decrease of lymphocyte subpopulations did not reach any statistical significance. The long-term myelotoxicity caused the decrease of LTC-IC that had a clinical correlation with the very difficult mobilization of PBSC. CONCLUSIONS: FND is efficient in treatment of follicular lymphoma. However myelotoxicity seems to be limiting. Myelotoxicity doesn't allow administering scheduled dose of FND in substantial amount of patients, long-term myelotoxicity complicates PBSC-mobilization. Lymphotoxicity is apparent, but seems not to be clinically important.
Keywords: Aged; Immunoglobulins; Antineoplastic Combined Chemotherapy Protocols; folikulární lymfom; imunoglobuliny; vidarabin; lymfocyty; protokoly protinádorové kombinované chemoterapie; lidé; lidé středního věku; senioři; ženské pohlaví; Lymphoma, Follicular; Dexamethasone; Female; mužské pohlaví; Adult; Middle Aged; mitoxantron; Vidarabine; Lymphocytes; Mitoxantrone; dexamethason; Humans; dospělí; kostní dřeň; Male; Bone Marrow